2018
DOI: 10.3389/fsufs.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Quality of Agricultural Soils Following Organic Material Additions Depend on Both the Quantity and Quality of the Materials Applied

Abstract: It is widely recognized that the application of organic materials is one of the most effective ways of increasing soil organic carbon (SOC) levels and improving soil quality, but do all forms of organic matter input have the same impact on soil properties A network of seven experimental sites investigated the effects on soil quality of annual applications over a minimum of 3 years of compost and food-based digestate in comparison with farmyard manure (FYM) and livestock slurry. Two of the sites were existing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Analysis of OM amended soil (at 20% compost) in comparison with the reference soil showed higher OM, N, and K content. These results are consistent with many studies, which indicated that compost addition increase OM and nutrients in amended soils (Adugna, 2018;Bhogal et al, 2018, Naba et al, 2020. In addition, compost, naturally, contributes to the stabilization and increase of crop productivity and crop quality (Adugna, 2018).…”
Section: Physico-chemical Properties Of Water Soil and Compostsupporting
confidence: 91%
“…Analysis of OM amended soil (at 20% compost) in comparison with the reference soil showed higher OM, N, and K content. These results are consistent with many studies, which indicated that compost addition increase OM and nutrients in amended soils (Adugna, 2018;Bhogal et al, 2018, Naba et al, 2020. In addition, compost, naturally, contributes to the stabilization and increase of crop productivity and crop quality (Adugna, 2018).…”
Section: Physico-chemical Properties Of Water Soil and Compostsupporting
confidence: 91%
“…(Please note that negative NECB values represent net CO 2 emission from grassland to the atmosphere.) The NECB of the slurry and FYM systems were similar to previously measured values in Japanese grasslands that respectively received only synthetic fertilizers or FYM + synthetic fertilizers [17], suggesting that slurry C had limited capacity for maintaining soil organic C in comparison with FYM C [12]. The emissions of N 2 O from grassland were not significantly different between slurry and FYM systems (2.2 Mg CO 2 -eq ha −1 y −1 in slurry system, 2.3 Mg CO 2 -eq ha −1 y −1 in FYM system), because synthetic N fertilizer was also applied [18,19].…”
Section: Necb and Emissions Of N 2 O And Ch 4 From Grasslandsupporting
confidence: 82%
“…On that basis, the identification of important processes with significant contributions is necessary in order to determine the priority of countermeasures to mitigate GHG. To date, it is recognized that the quality and quantity of organic materials applied have great influence on soil organic carbon [4,12]; however, insufficient information is available on the effect of manure type (i.e., slurry or FYM) on the net GHG emissions and GHGI of herbage production systems.…”
Section: Introductionmentioning
confidence: 99%
“…This condition shows that the liquefaction-affected lands from the physical aspect can still be used as agricultural areas, however it requires input to increase the nutrient availability in order to optimize the soil health and the carrying capacity for the plant growth. The administration of the organic materials input can improve the soil structure and the water holding capacity [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%